OPTIMIZATION OF THE USE OF MEDIA INFORMATICS IN GRADE OF FIVE DURAJAYA STATE ELEMENTARY SCHOOL - Setiawati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Informatics media is needed as a support in education in elementary schools, for various purposes including learning media. Besides being used for learning media, information technology can also be used to develop knowledge. and Implementation of the National Assessment is a government program in implementing ANBK (Computer-Based National Assessment) which was rolled out by the Minimum Competency Assessment (AKM) program. AKM preparation activities are carried out in schools and for the implementation of a Computer-based National Assessment with the option of Online mode or Semi-Online mode with the need for infrastructure, one of which is a computer or laptop and adequate internet network. The ANBK program aims to be able to expedite AKM activities which are designed to produce information that triggers quality improvements that can capture fundamental competencies in various subjects in grade five. Based on the results of a study on the implementation of the Computer-based National Assessment with the option of Online mode or Semi-Online mode at Durajaya Curugkembar Public Elementary School, Sukabumi Regency, it can provide an overview by forming the competency and personality of students regarding Teachers as Learning Agents, Teacher Roles, Implementation of National Assessments, and Use Informatics Media